2006
DOI: 10.1523/jneurosci.1419-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Branch-Specific Ca2+Influx from Na+-Dependent Dendritic Spikes in Olfactory Granule Cells

Abstract: Two-photon laser scanning microscopy was used to correlate electrical events detected with whole-cell somatic recordings to Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 36 publications
5
48
0
Order By: Relevance
“…3), we reasoned that granule cells are likely to be the major cell type contributing to the large increase in miniature IPSCs observed in our experiments. In addition, the persistence of DHPG-evoked spontaneous IPSCs in the presence of TTX, but their elimination by blockers of VGCCs, is consistent with studies in granule cells demonstrating that local or global calcium spikes are potential triggers of transmitter release (Egger et al, 2003(Egger et al, , 2005Midtgaard, 2003, 2005;Zelles et al, 2006). Thus, one possible mechanism for the action of DHPG is via direct depolarization of granule cells.…”
Section: Mechanisms Of Mglur1 Action In Granule Cellssupporting
confidence: 82%
“…3), we reasoned that granule cells are likely to be the major cell type contributing to the large increase in miniature IPSCs observed in our experiments. In addition, the persistence of DHPG-evoked spontaneous IPSCs in the presence of TTX, but their elimination by blockers of VGCCs, is consistent with studies in granule cells demonstrating that local or global calcium spikes are potential triggers of transmitter release (Egger et al, 2003(Egger et al, , 2005Midtgaard, 2003, 2005;Zelles et al, 2006). Thus, one possible mechanism for the action of DHPG is via direct depolarization of granule cells.…”
Section: Mechanisms Of Mglur1 Action In Granule Cellssupporting
confidence: 82%
“…Several studies have reported dendritically localized spiking in GCs, though often involving primarily low-threshold Ca 2+ spikes (Egger et al 2003(Egger et al , 2005. Spontaneous fast Na + -based dendritic spikes have been reported in frog GCs under basal (unstimulated) conditions (Zelles et al 2006). If also present in mammals, spontaneous "D-spikes" could function to synchronize multiple dendrodendritic release sites in one GC, enabling coincident inhibition of nearby pairs of principal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that latencies are glomerulus specific indicates that the biophysical mechanisms that give rise to the long latencies must be in some respect input specific. This may be attributable to different inputs activating different dendritic branches of the granule cell (Zelles et al, 2006) or otherwise to different properties of synapses onto the granule cells. The biophysical mechanisms underlying this unique behavior are unclear, but understanding them will be important as we try to understand the functional role of granule cells in olfactory bulb circuitry.…”
Section: Discussionmentioning
confidence: 99%